Mengenal Teori-Teori Belajar - Ramses Simanjuntak (Sekolah Tinggi Theologia Nazarene Indonesia, 2018)
Signs of people learn can be seen from the occurrence of transformation in a person. Transformation is a change of behavior. Behavioral change touches the three domains of education within the learner, the cognitive domain, the affective domain, and the psycotor realm or better known as the domain of knowledge, the sphere of attitude, and the skill domain. Learning is essentially a change that occurs within a learner after the end of a learning activity. Because after a person ends learning activities there is usually knowledge and insight informed to the learner, which makes the learner think and contemplate the results of learning, so he can take a decision from the learning results.